BODY COMPOSITION OF ELDERLY GOERS RESISTIVE EXERCISE AND HEALTH PROJECT (LERES/UEPA) IN 2012. (Fiep Bulletin - online, 2013)
Aim of the study was to evaluate the body composition of elderly goers resistive exercise and health project (LERES/UEPA) in 2012.Pointing percentage of caloric adequacy of macro and micronutrients, assessing 22 seniors enrolled in the program, aged less than sixty (60) years, of both sexes. Anthropometric assessment was performed by checking the values ??of body weight and height to calculate body mass index (BMI), skinfolds, circumferences waist / hip ratio for subsequent estimation of the percentage of body fat and risk of cardiovascular disease of the elderly; and calf circumference to estimate the loss of muscle mass. BMI showed low percentages of malnutrition (9.1%), and the majority is divided between Normal weight (45.5%) and overweight (45.5%). Already the circumference of the calf 95.5% of elderly people lies on eutrophy. In relation to waist / hip ratio 63.7% of participants showed no risk of developing cardiovascular disease and 36.3% of the elderly are above the reference value, presenting the risk of developing cardiovascular disease.
Keywords: elderly; resistance exercise; health; quality of life.